Producer services and trade liberalization - Breinlich, Holger (John Wiley & Sons, Ltd, 2016)
Trade liberalization and recent advances in communication and information technologies increasingly permit the trade of producer services across borders. This entry discusses research on the nature and importance of such trade, and on the consequences of services trade liberalization. Trade in producer services now accounts for close to 70% of services trade and 14% of total world trade. Services trade liberalization has figured prominently in multilateral negotiations in the World Trade Organization and in many regional trade agreements. Progress in liberalizing services trade has been slow, however, and has been achieved mainly via unilateral initiatives. As a consequence, important barriers remain across many countries and types of services. This is despite the fact that a small but growing body of research has shown that trade liberalization in producer services can have substantial positive economic effects.